Surveying the Contamination Rate, Sensibility and Antimicrobial Resistance Patterns in Staphylococcus Aureus Isolated from Traditional Cheese Consumed in Qotur of khoy Province - Hamed Molla Abaszadeh; Begnood Haji Sheikhzadeh (Fasa University of Medical Sciences, 2014)
Background ; Objective: Milk and dairy products are good nutritional environments for bacterial growth. Different types of bacteria can quickly contaminate them and as a result, these products cause disease in human after transmission. Staphylococcus aureus is among the bacteria of milk and dairy products that cause disease in human. With regard to the point that traditional cheese(unpasteurized) is produced in not a sanitary situation among the residents of border and rural areas of northwest of Iran, the objective of this study was to evaluate the contamination rate, sensibility and antimicrobial resistance patterns in Staphylococcus aureus isolated from traditional cheese consumed in Qotur of khoy province. Materials & Methods: This cross-sectional study was performed on 80 cheese samples provided from different dairy products stores of Qotur town in Khoy city during in the first six months of the year 2011. After collecting the samples, they were transported to the laboratory. Results: among 80 studied samples, 16 samples (20%), 40 samples (50%), and24 samples (30%) were produced from cow milk, sheep milk, and a mixture of cow and sheep milk, respectively. 40 samples (50%) showed contamination by Staphylococcus aureus. Antibiotic resistances to Methicillin, Tetracycline and Cotrimoxazole, and Oxacilina were seen in four samples (9.3%), two samples (4.65%), and one sample (2.33%), respectively. Conclusion: Considering the high contamination rate of traditional cheese by Staphylococcus aureus in this area, respective experts should control its production and distribution.  Efficient informing about the risk of using these products seems necessary.